Treacherous coattails: gubernatorial endorsements and the presidential race in Kenya's 2017 election. Issue 2 (3rd April 2019) - Gadjanova, Elena
ABSTRACT: Could there be coattail effects in the absence of strong parties? How would such effects manifest in countries with ethnic and personality-based politics? Kenya's 2017 election presents an opportunity for a theoretical and empirical contribution to the study of coattail effects in plural societies. With the newly-created and highly attractive positions of county governors, down-ticket races became a lot more competitive, forcing parties to make difficult choices: which races to focus on, how to apportion limited resources across the ballots, and how to forge alliances with local leaders whose networks were key to success in the battlegrounds. Presidential candidates found themselves in a precarious position: endorsing governor aspirants in competitive races could cause a backlash, failing to endorse could signal a lack of confidence in key figures and jeopardize all six positions on the ballot. I argue that coattail effects in Kenya's 2017 election were conditional on governors receiving clear and public endorsements by the presidential candidates and that effects flowed from presidential candidates to governor aspirants in parties' strongholds, and vice-versa in battleground counties. The findings have implications for theories of coattail effects, campaign strategy, legislative fragmentation, and citizen-politician linkages in settings with personality-based politics and weakly-institutionalised parties.